Productive and Economic Comparison Between Aquaponics and Hydroponics in Different Seasons - Estrada-Perez, Nallely; Hernandez-Llamas, Alfredo; Ruiz-Velazco, Javier M. J. (REVISTA TERRA LATINOAMERICANA, 2025)
The productive and economic performance of experimental aquaponic and hydroponic (NFT Technique) systems for the production of tilapia (Oreochromis niloticus), lettuce (Lactuca sativa) and cucumber (Cucumis sativus) are evaluated. Two plant production cycles and a single fish production cycle were analyzed. The systems were compared regarding production and economic benefits. Production of 21.33 kg m-3 of fish, 9.75 pieces of lettuce m-2, and 0.0083 kg m-2 of cucumber was obtained in the aquaponic system. In the hydroponic system, a production of 10.49 pieces of lettuce m-2 and 0.94 kg m-2 of cucumber fruit was obtained. The benefit-cost ratios were 1.50 in the aquaponic system and 2.18 in the hydroponic system, while the aquaponic system was superior regarding net profit (US$ 36 693.32 ha-1) than the hydroponic system (US$ 24 313.42 ha-1). It is concluded that the hydroponic system had higher plant production; however, aquaponics is more profitable due to the production of fish and vegetables.